Correlation between Inflammation and Fibrinolysis Impairment on Central Obesity: A Study for hsCRP, PAI-1, PAP and TAFI - Winni Agustiani; Mansyur Arif; Ilhamjaya Patellongi (The Indonesian Biomedical Journal, 2011)
BACKGROUND: Inflammation in the vascular wall plays an important role in the pathogenesis of atherosclerosis. Current studies have shown that increase of systemic inflammatory marker like the acute phase component C-reactive protein (CRP) are associated with an unfavorable progression of disease and an increased risk for acute cardiovascular events. Recently, a close association of Metabolic Syndrome (MetS) with hemostatic abnormalities has been reported. Among hemostatic abnormalities, an increase in plasminogen activator inhibitor (PAI)-1, a strong inhibitor of fibrinolysis, is considered a core feature of MetS. High PAI-1 concentrations may be associated with thrombus formation, also causing cardiovascular events. Therefore, we investigated the association between markers for chronic inflammation (CRP) and the markers of fibrinolytic impairment (PAI-1, PAP, TAFI) in subjects with central obesity.METHODS: This was a cross-sectional study in 80 male Indonesian subjects, aged 30-60 years old with central obesity, conducted from January to March 2008 in Bandung.RESULTS: The study results showed that there was a difference of PAI-1 levels between MetS and Non-MetS group. There were significant correlations between hsCRP and PAI-1 (r=0.252, p=0.024 ), hsCRP and PAP (r=0.253, p=0.024), and also between PAI-1 and PAP (r=-0.239, p=0.033 ) respectively. But, no correlation found between hsCRP and TAFI.CONCLUSIONS: There was correlation between inflammation and fibrinolysis impairment on central obesity. Concentrations oh hsCRP, PAI-1 and TAFI were significantly higher in MetS.KEYWORDS: inflammation, fibrinolysis impairment, hsCRP, PAI-1, PAP, TAFI